Lightning Performance Analysis Of A Rooftop Grid-connected Solar Photovoltaic Without External Lightning Protection System - M. S. M. Nasir; M. Z. A. Ab-Kadir; M. A. M. Radzi; M. Izadi; N. I. Ahmad; N. H. Zaini (PLOS ONE, 2024)
Nasir MSM, Ab-Kadir MZA, Radzi MAM, Izadi M, Ahmad NI, Zaini NH (2019) Lightning performance analysis of a rooftop grid-connected solar photovoltaic without external lightning protection system. PLoS ONE 14(7): e0219326. https://doi.org/10.1371/journal.pone.0219326